Culture independent analysis using gnd as a target gene to assess Escherichia coli diversity and community structure. - Cookson AL; Biggs PJ; Marshall JC; Reynolds A; Collis RM; French NP; Brightwell G (My University)
Current culture methods to investigate changes in Escherichia coli community structure are often slow and laborious. Genes such as gnd (6-phosphogluconate dehydrogenase) have a highly variable nucleotide sequence and may provide a target for E. coli microbiome analysis using culture-independent methods. Metabarcoded PCR primers were used to generate separate libraries from calf faecal samples for high throughput sequencing. Although a total of 348 separate gnd sequence types (gSTs) were identified, 188 were likely to be due to sequencing errors. Of the remaining 160 gSTs, 92 did not match those in a database of 319 separate gnd sequences. 'Animal' was the main determinant of E. coli diversity with limited impact of sample type or DNA extraction method on intra-host E. coli community variation from faeces and recto-anal mucosal swab samples. This culture-independent study has addressed the difficulties of quantifying bacterial intra-species diversity and revealed that, whilst individual animals may harbour >50 separate E. coli strains, communities are dominated by <10 strains alongside a large pool of subdominant strains present at low abundances. This method will be useful for characterising the diversity and population structure of E. coli in experimental studies designed to assess the impact of interventions on the gut microbiome.